Non‐Bonded Radii of the Atoms Under Compression. Issue 21 (15th October 2020) - Rahm, Martin; Ångqvist, Mattias; Rahm, J. Magnus; Erhart, Paul; Cammi, Roberto
Abstract: Abstract : We present quantum mechanical estimates for non‐bonded, van der Waals‐like, radii of 93 atoms in a pressure range from 0 to 300 gigapascal. Trends in radii are largely maintained under pressure, but atoms also change place in their relative size ordering. Multiple isobaric contractions of radii are predicted and are explained by pressure‐induced changes to the electronic ground state configurations of the atoms. The presented radii are predictive of drastically different chemistry under high pressure and permit an extension of chemical thinking to different thermodynamic regimes. For example, they can aid in assignment of bonded and non‐bonded contacts, for distinguishing molecular entities, and for estimating available space inside compressed materials. All data has been made available in an interactive web application. Abstract : Van der Waals radii are useful tools for analyzing and rationalizing chemical structure under ambient conditions. But what are the corresponding non‐bonded radii of atoms at conditions of high pressure? This work presents theoretical estimates of radii of 93 atoms, in the absence of chemical bonding, in a pressure range from 0–300 gigapascals.